2012
DOI: 10.1590/s1809-98232012000400016
|View full text |Cite
|
Sign up to set email alerts
|

Idosos residentes em instituições de longa permanência para idosos da região metropolitana de Belém-PA

Abstract: Estudo exploratório-descritivo realizado em quatro instituições de longa permanência para idosos (ILPI), duas filantrópicas e duas governamentais, na região metropolitana de Belém, PA. OBJETIVO: Descrever as características sociais do idoso institucionalizado de baixa renda, em ILPI da região metropolitana de Belém, e identificar as condições de vida, de saúde e o grau de dependência nas atividades básicas de vida diária. METODOLOGIA: Participaram 165 idosos institucionalizados que se limitaram a descrever os … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
18

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 7 publications
1
5
0
18
Order By: Relevance
“…In this regard, studies show a progressive increase in the institutionalization of the elderly. 12,13 In evaluating the principal threats to the health of the elderly in the LCTFs that participated in this study, chronic diseases were found in 165 patients (66.0%), which shows that the process of aging generates a significant change in the patterns of morbimortality. 14 However, sequelae arising from chronic diseases or those which have degenerative characteristics, in addition to the alterations brought about by senescence itself and the context of coexisting with other elderly patients and sharing physical spaces (rooms, bathrooms, cafeterias) in LCTFs, increases the risk of infection.…”
Section: Discussionmentioning
confidence: 86%
“…In this regard, studies show a progressive increase in the institutionalization of the elderly. 12,13 In evaluating the principal threats to the health of the elderly in the LCTFs that participated in this study, chronic diseases were found in 165 patients (66.0%), which shows that the process of aging generates a significant change in the patterns of morbimortality. 14 However, sequelae arising from chronic diseases or those which have degenerative characteristics, in addition to the alterations brought about by senescence itself and the context of coexisting with other elderly patients and sharing physical spaces (rooms, bathrooms, cafeterias) in LCTFs, increases the risk of infection.…”
Section: Discussionmentioning
confidence: 86%
“…O mesmo avalia a capacidade do idoso na alimentação, banho, vestuário, transferência da cama para a cadeira e viceversa, locomoção ao sanitário e continência (POLARO et al, 2012). Foram considerados independentes os idosos que informaram não precisar de ajuda em nenhuma dessas atividades.…”
Section: Introductionunclassified
“…With the process of aging, there is an increasing demand for LTCIEs, considered as alternative housing, [4][5][6] and a form of health care. 7 The coverage of this mode of living is lacking, however, perhaps reflecting the negative image that institutionalization produces.…”
Section: Introductionmentioning
confidence: 99%
“…10 Studies of institutionalization of the elderly overlook data from a considerable portion of this population, those on waiting lists for a place in an LTCIE. While there are occasional mentions of the existence of such individuals, 5,6 no description of this population group was found in Brazilian literature.…”
Section: Introductionmentioning
confidence: 99%